Person-Centered Care in Nursing Homes: Potential of Complementary and Alternative Approaches and Their Challenges. (March 2022) - Bhattacharyya, Kallol Kumar; Craft Morgan, Jennifer; Burgess, Elisabeth O.
A person-centered approach to care shifts the mind-set of care partners from a traditional medical model to a social model in managing chronic conditions. Using a qualitative descriptive approach, this study examines the barriers and facilitators to the implementation of person-centered care (PCC) and how the integration of complementary and alternative approaches (CAA) has the potential to improve residents' quality of life in nursing homes (NHs). Findings indicate that NHs offer a wide range of engagement activities, but these activities are not purposefully integrated into a person-centered plan of care. Factors such as turnover, "working short, " supervisor support, and rising resident care needs make it challenging to implement PCC in NHs. This knowledge of the landscape of activities will help us identify and improve strategies for supporting residents at a deeper, more meaningful level. CAA has the potential to be therapeutic for residents if integrated into collaborative approaches to care.